Déficit magnocelular e estresse visual associados à dificuldade de leitura : conceituação, avaliação e intervenção - Douglas de Araújo Vilhena (2021)
Most studies in cognitive psychology agree that a disturbance in phonological processing and oral language is the best theoretical models for explaining the etiology of reading difficulties. Although these models are correct in terms of the importance of grapheme–phoneme conversion to access the semantic system, it is not realistic to disregard the role of visual processing as an input to the orthographic-visual analysis system of graphemes. Visual stress is a visual processing disorder, resulting from a deficit in the magnocellular visual system, specifically characterized by the presence of visual-perceptual distortions in the text and progressive visual discomfort during reading, independent of problems in visual acuity. The main objective of this doctoral thesis was to investigate participants with visual stress associated with reading difficulty, by means of instruments that assess the visual magnocellular system (ie, doubled frequency perimeter and ocular tracker), as well as to verify if there is support in the literature and empirically for intervention with the use of spectral overlays in reducing visual stress. The present thesis was composed of three studies, one systematic review of the literature and two experimental studies, complemented by psychometric evidences from the Reading Tests Battery. In the first study, 12 experimental articles were reviewed, and it was verified that spectral overlays are a safe, non-invasive, and relevant intervention to reduce visual stress (headache, eye pain, visual-perceptual distortions) and improve the different visual parameters (accommodation, eye movement), reading (reading rate, relative efficiency, and comprehension) and facial recognition. The second study found that, on average, participants with a confirmed diagnosis of Developmental Dyslexia, assessed by means of temporal processing assessment instruments (ie, doubled frequency perimeter and ocular motor skills), have deficits consistent with visual magnocellular dysfunction, when compared to the paired control group. Finally, in the third study, participants with visual stress (184 children and 139 adolescents), using spectral overlays, significantly improved eye motor skills (less fixations and regressions), with an increase in positive factors (Perceptual Recognition, Reading Rate, Relative Efficiency, Comprehension). The present thesis corroborates with the literature that considers that the reading difficulty is partially related to a deficit in the visual magnocellular system, with consequent disturbance of the visual processing, of the temporal processing, of eye movements control, expressing by a visual stress. The intervention with the use of spectral overlays can help readers to reduce symptoms of visual stress and increase visual comfort.